Investigating the Impact of Website Quality on Consumers' Satisfaction in Jordanian Telecommunication Sector - Excimirey Amer Al-Manasra; Mohammed Khair Saleem Abu Zaid; Fadi Taher Qutaishat (Arab Economic and Business Journal, 2013)
As Jordanian telecommunication organizations have begun increasingly to communicate and interact with their consumers via the Web, providing such a service has demanded acute understanding of consumers' requirements and appropriate provision of solutions. In this paper, we examined the impact of Websites quality (which was measured by usability, information quality and service interaction) of four major Jordanian telecommunication organizations on the consumer's satisfaction. Survey results of 84 students, from the faculty of planning and management at Al-Balqa' Applied University, have been collected and then analyzed using descriptive statistics and hierarchical regression. The results of this study showed that the usability and services interaction were highly significant factors that directly affected the consumers' satisfaction according to the testing model.
Keywords: 650; website quality; usability; information quality; service interaction